A Systematic Review and Integrated Bioinformatic Analysis of Candidate Genes and Pathways in the Endometrium of Patients With Polycystic Ovary Syndrome During the Implantation Window - Zulazmi Sutaji; Marjanu Hikmah Elias; Mohd Faizal Ahmad; Abdul Kadir Abdul Karim; Muhammad Azrai Abu (Frontiers, 2024)
Indexed by WOS/SCOPUS/ERA